2011
DOI: 10.1002/iroh.201111247
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Ecology of Hyalella sp. (Crustacea: Amphipoda) in a High Andes Headwater River with Travertine Deposits

Abstract: We studied the diet of 50 individuals of Hyalella sp. collected in the karstic headwaters of a highaltitude Andean river (3817 m a.s.l. Peru) in four different habitats: macrophytes, bryophytes, leaf litter, and layers of travertine. The gut content analysis showed a dominance of fine particulate organic matter (FPOM) in most habitats -layers of travertine (69.5%), Myriophylum (58.5%) and bryophytes (56.8%) -except for individuals collected in leaf litter where coarse particulate organic matter (CPOM) represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Of those Sphaeriidae, Planorbidae, Lymnaeidae, Physidae, Hydrobiidae and Ancylidae are the only families that have been reported in Andean areas above 2 000masl (Posada et al, 2000;Carrera & Gunkel, 2003;Jacobsen, 2004) and were the only ones included in our index. Benthic Crustacea reported in Andean areas includes: Ostracoda and Hyalellidae (Amphipoda) (Vásconez, 2000;Ríos-Touma, 2004;Ríos-Touma & Prat, 2004;Acosta & Prat, 2011). Hyalella is the only freshwater Hyalellidae genera present in South America (Peralta, 2001), but we kept this taxon as a family for the index.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of those Sphaeriidae, Planorbidae, Lymnaeidae, Physidae, Hydrobiidae and Ancylidae are the only families that have been reported in Andean areas above 2 000masl (Posada et al, 2000;Carrera & Gunkel, 2003;Jacobsen, 2004) and were the only ones included in our index. Benthic Crustacea reported in Andean areas includes: Ostracoda and Hyalellidae (Amphipoda) (Vásconez, 2000;Ríos-Touma, 2004;Ríos-Touma & Prat, 2004;Acosta & Prat, 2011). Hyalella is the only freshwater Hyalellidae genera present in South America (Peralta, 2001), but we kept this taxon as a family for the index.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, these values are consistent with the presence of these taxa in a wide range of water conditions (Machado et al, 1997; Viña-Vizcaíno & Ramírez-Gonzáles, 1997;Jacobsen & Encalada, 1998;Vásconez, 2000;Ríos-Touma, 2004;Ríos-Touma & Prat, 2004). Hyalellidae is found in a wide variety of habitats, shows diverse feeding strategies (Peralta, 2001;Acosta & Prat, 2011), and is resistant to certain types of organic pollution (Jacobsen & Encalada, 1998). Therefore, we used the score for Gammaridae (6) from the index developed by Armitage et al (1983), which is consistent with the frequent presence of this family in reference to mildly impaired streams.…”
Section: Tolerance To Pollutionmentioning
confidence: 99%
“…Many studies have reported that Chironomidae and Oligochaeta are important colonizers of artificial substrates (Carvalho & Uieda 2004, Souza et al 2008, Barker et al 2014. However, on Amphipoda most information refers its taxonomy, biology, ecology, and their association with aquatic macrophytes and macroalgae (Jacobucci & Leite 2002, Saigo et al 2009, Acosta & Prat 2011, Bastos-Pereira & Bueno 2013. A study on temporal and spatial patterns of macroinvertebrates associated with different floating macrophytes revealed that when the area covered by R. natans is large, the macroinvertebrate community is dominated by Hyalella curvispina amphipodes Oecol.…”
Section: Discussionmentioning
confidence: 99%
“…Aust., 21(4): 407-421, 2017 (Fontanarrosa et al 2013). Amphipoda individuals are commonly found in association with macrophytes and macro-algae (Jacobucci & Leite 2002) and present an herbivorous or herbivorous-detritivorous feeding habit (Jacobucci & Leite 2006, Saigo et al 2009, Acosta & Prat 2011, Barker et al 2014. This peculiarity of these organisms can explain the dominance of crustaceans in R. natans and S. intermedia stands, attaining approximately 50% of the relative abundance.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced detrital processing is ecologically meaningful because Hyalella and other members of the shredder guild consume high amounts of detrital material in the field (Acosta and Prat 2011). This assertion is supported by studies with another leaf shredding amphipod (i.e., Gammarus), which is a key organism in the leaf decomposition process in Central European rivers (e.g., Dangles et al 2004).…”
Section: Implications Of Sedimite ® In Organic Matter Processingmentioning
confidence: 95%